The risk factors for anxiety amongst health care workers in Primary Health care center during COVID 19 pandemic : - Fisekovic Kremic, Marina (General Practice, 2022)
The coronavirus disease 2019 (COVID 19) pandemic killed millions of people and affected the whole world, including Serbia. Healthcare workers could not isolate themselves from patients. They worked under adverse and challenging conditions, which could have caused mental health problems. This study aimed to identify the risk factors for anxiety in healthcare workers working in Covid wards (CW) of Primary Healthcare center (PHC). Method: This cross-sectional study was conducted among healthcare workers of the CWs. During the study period, we had a total of 150 completed questionnaires. Descriptive statistics, Pearson chi-square test, and Pearson correlation were used to analyze the data. We used SPSS for data analysis. Results: Our sample included 150 healthcare workers (HCWs), of whom 86.0% were females, the majority were 41-50 years of age (40,0%), and have been working for 21- 30 years (32,7%). In our sample, 94,6% HCWs stated they received personal protective equipment (PPE). The results revealed a significant association only between gender and anxiety. Anxiety was higher among females than males. Correlation analysis indicated the feeling of anxiety was positively correlated with the workload, exhaustion, and family strain. The feeling of anxiety was not correlated with the feeling of protection. The feeling of protection was in negative correlation with family strain. Conclusion: Anxiety was present in HCWs during the pandemic. Gender is the risk factor for anxiety in HCWs who work in CWs in PHCs.